Hysteresis and Nairu in the Euro Area - Camille Logeay; Silke Tober (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2005)
This paper analyses the Nairu in the Euro Area and the influence that hysteresis had on its development. Using the Kalman-filter technique we find that the Nairu has varied considerably since the early seventies. The Kalman-filter technique is applied here using explicit exogenous variables. In order to test for hysteresis, the dependence of the Nairu on actual unemployment and long-term unemployment is estimated and found to be significant for the Euro Area and Germany respectively. The existence of hysteresis effects implies the possibility of a long-run non-superneutrality of monetary policy.
urn:nbn:de:101:1-2008081478
Keywords: C32; E32; E52; 330; Nairu; hysteresis; Kalman Filter; Phillips curve; superneutrality